Characterizing a landmark biomass-burning event and its implication for aging processes during long-range transport. (15th November 2020) - Nguyen, Ly Sy Phu; Huang, Hsiang-Yu; Lei, Tin Long; Bui, Thu Thuy; Wang, Sheng-Hsiang; Chi, Kai Hsien; Sheu, Guey-Rong; Lee, Chung-Te; Ou-Yang, Chang-Feng; Lin, Neng-Huei
Abstract: Springtime biomass burning (BB) in peninsular Southeast Asia (PSEA) has a large impact on the downwind air quality as has been frequently observed at the Lulin Atmospheric Background Station (LABS). Numerous PSEA BB long-range transport events have been observed at LABS in the past decade, of which the biggest event (based on the carbon monoxide (CO) mixing ratio and particulate matter (PM) loading) occurred on March 18, 2009. In this study, for the first time, in-situ observations from LABS, MERRA-2 reanalysis data, and satellite data were combined to elucidate this remarkable event. This event lasted over 29 h and seriously impacted the air quality at LABS. Average concentrations (±S.D.) of CO, ozone (O3 ), and PM10 were 586.2 ± 164.5 ppb, 105.2 ± 23.4 ppb, and 90.4 ± 24.4 μg m −3, respectively, which were enhanced ranging from 98% to 280% over the March 2009 average. Furthermore, significant increases in toxic air pollutants (e.g., gaseous elemental mercury (GEM) and dibenzo-p-dioxin/furan) concentrations were also observed, implying a severe impact from BB smoke on ecosystems and human health. The transport pathway and BB smoke layer height were investigated with backward trajectories, daily satellite aerosol products, and lidar observations. The mean SSA440 value of 0.87 suggested that the plume contained highly adsorbing aerosols, and the high char-EC/soot-EC ratio (low-temperature elemental carbon/high-temperature elemental carbon) of 29.4 suggested predominance of BB aerosols. In addition, plume aging indicators (e.g., ΔGEM/ΔCO, ΔO3 /ΔCO, char-EC/soot-EC) suggest the BB plume was only weakly aged (i.e. low air mass intermixing, low chemical transformation, low cloud interaction) and in a nearly pristine state during the whole of the long-range transport. This event study can serve as a valuable benchmark when identifying unaged BB plumes that have been transported from PSEA to LABS (>2000 km) and will be useful for characterizing PSEA BB and its impact on greater Asia environment. Graphical abstract: Image 1 Highlights: A big smoke plume transport to remote site was illustrated by multi-platform datasets. Concentrations of air pollutants including toxins increased significantly during event. Limited aging process of smoke plume was found despite fairly long-distance traveling. Criteria for identifying long-range transported events experiencing less aging processes.